(untitled) (The Pakistan Development Review, 2006)
The use of social and economic indicators to evaluate and rank governments’ performance is often found in literature. The Anglo-Commonwealth and Scandinavian countries rest on the surveillance of work in the various ministries. This performance accounting approach thus becomes crucial for any regime to perform superlatively to their predecessors and thus it provides the basis to suggest why it is important to inspect governance of a government. Government’s efficacy also depends on the magnitude of the welfare that it is able to achieve. Debate on welfare is dated back to Adam Smith at-least. Now the question is what should be the welfare gauging indicators. We understand that, issues related to poverty, land utilisation, agriculture and industrial sectors, health services, education, growth rate of national income, per capita income, employment, etc. are important factors that can explain welfare status of a nation. Thus by developing an index based on performance in these areas, various political regimes can be evaluated and ranked. These evaluations and rankings set standards for future governments to improve. Thus these studies can be useful for developing and improving social welfare standards.